Ciliary Neurotrophic Factor Activated Signaling Pathways in Retinal Müller Cells - P. Sarthy Vijay; Topgi Shobha; Joseph Dudley V. (Journal of Ophthalmic Science, 2016)
Ciliary neurotrophic factor (CNTF) is a well-tested, neuroprotective agent that has been shown to retard photoreceptor degeneration in several animal models of retinitis pigmentosa. The molecular mechanisms underlying CNTF-mediated neuroprotection are currently not understood. CNTF could act directly on photoreceptors or it could act indirectly by stimulating Müller glial cells to produce photoreceptor neuroprotective agents. To better characterize CNTF action on Müller cells, we have studied signaling pathways activated by CNTF using an established retinal Müller cell line, rMC-1. RNA was isolated from CNTF-treated cultures, and suppressor of signal transducer and activator of transcription (SOCS3) and Glial fibrillary acidic protein (GFAP) transcript levels were assessed by quantitative real-time PCR. Immunoblotting was used to examine activation ofmitogen activated protein kinase (ERK1/2/MAPK) and phosphoinositide 3-kinase (PI3-K)/Aktpathways in response to CNTF. Additionally, the level of5' AMP-activated protein kinase (AMPK), an enzyme that plays a key role in cellular energy homeostasis levels, was determined by immunoblotting. CNTF treatment resulted strong upregulation of SOCS3 and GFAP transcripts that were blocked by expression of a dominant-negative STAT3 mutant. CNTF treatment also resulted in transient activation of ERK1/2/MAPK but not PI3K/Akt signaling pathway. There was no change in activation of AMPK. We conclude that CNTF treatment leads to stimulation of JAK-STAT and MAPK signaling pathways but not the PI3K/AKT pathway, associated with cell death, in Müller cells.
Keywords: Neuroprotection